2018
DOI: 10.3390/ma11091665
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Properties of Decellularized Extracellular Matrix-Coated 3D Printed Poly(ε-caprolactone) Nerve Conduits for Promoting Schwann Cells Proliferation and Differentiation

Abstract: Although autologous nerve grafting remains the gold standard treatment for peripheral nerve injuries, alternative methods such as development of nerve guidance conduits have since emerged and evolved to counter the many disadvantages of nerve grafting. However, the efficacy and viability of current nerve conduits remain unclear in clinical trials. Here, we focused on a novel decellularized extracellular matrix (dECM) and polydopamine (PDA)-coated 3D-printed poly(ε-caprolactone) (PCL)-based conduits, whereby th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Novel decellularized extracellular matrix (dECM) and PDA-coated 3D printed PCL-based conduits were created for nerve regeneration. The presence of PDA significantly improved the hydrophilicity and mechanical properties of conduits, as well as cellular behaviors and neuronal differentiation of Schwann cells (Chen C. et al, 2018). Similarly, the PDA coating significantly improved the hydrophilicity and cytocompatibility of fabricated carbon scaffolds.…”
Section: Pda-related Bioengineering In the Peripheral Nerve Regenerationmentioning
confidence: 85%
“…Novel decellularized extracellular matrix (dECM) and PDA-coated 3D printed PCL-based conduits were created for nerve regeneration. The presence of PDA significantly improved the hydrophilicity and mechanical properties of conduits, as well as cellular behaviors and neuronal differentiation of Schwann cells (Chen C. et al, 2018). Similarly, the PDA coating significantly improved the hydrophilicity and cytocompatibility of fabricated carbon scaffolds.…”
Section: Pda-related Bioengineering In the Peripheral Nerve Regenerationmentioning
confidence: 85%
“…Putting it simply, Col I and FN are adsorbed onto the surface of materials and thus basically act as a biological platform for further cellular attachment. As such, it has been reported that different quantities of ECM protein present on surfaces heavily determines the levels of cellular adhesion, which in turn influences cellular behavior [45]. Our study showed that hybrid CS–CH coated Ti–6Al–4V scaffolds can be used as a potential surface modification technique and that they have the ability to enhance the expression of Col I and FN proteins due to improved initial cell adhesion with the surface of the Ti–6Al–4V scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…However, these outcomes are not satisfactory and various improvements to these methods have been investigated (Eren, Öksüz, Küçükodaci, et al, 2016). Many studies have reported that tubular materials in which a cellular component is combined with a neurotropic factor and extracellular matrix (ECM) increases the regenerative potential (Chen, Yu, Ng, et al, 2018;Ren, Faust, Van Der Merwe, et al, 2018). In these reports, biodegradable synthetic tubular materials, including poly(lactide-co-glycolide) (Nune, Subramanian, Krishnan, Kaimal, & Sethuraman, 2017) or chitosan tubes (Meyer, Wrobel, Raimondo, et al, 2016) have been used.…”
mentioning
confidence: 99%